2009
DOI: 10.1002/cjoc.200990227
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Application of Some Azo and Azomethine Dyes Containing Pyrazolone Moiety

Abstract: 3-Amino-1-phenyl-4,5-dihydro-1H-pyrazol-5-one (1) was used as starting material for the synthesis of a number of azo compounds 3a-3c and azomethine derivative 4. The deblocking of 3a-3c and 4 gave rise to 5a-5c and 6 in which a free amino was revealed. The diazonium salts of 5a-5c and 6 were coupled with several phenols to produce a number of bis azo compounds 7a-7c and 8a-8c with azomethine in position 4 and azoic group in position 3. The prepared dyes were structurally confirmed by elemental analysis, spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Total dyeing time was 90 min. It was then cooled to 60 °C and then after washing, dyed samples were rinsed and dried …”
Section: Methodsmentioning
confidence: 99%
“…Total dyeing time was 90 min. It was then cooled to 60 °C and then after washing, dyed samples were rinsed and dried …”
Section: Methodsmentioning
confidence: 99%
“…In accordance with literature procedures, the compounds 1,3-disubstituted-1H-pyrazol-5(4H)-ones 1a-h, 36 1,3-disubstituted-1H-pyrazole-4,5-diones derivatives 2a-h, 37 4-benzylidene-1,3-diaryl-1H-pyrazol-5(4H)-one 3a-h 38 and 4-phenylazo-1,3-diaryl-1H-pyrazol-5(4H)-one 4a-h 39 were synthesized. To synthesize a series of novel azomethine dyes, we tried three different methods: A, B, and C. 31,40 Actually, we found that method A was simple, had a short reaction time and had a high reaction rate and excellent yields.…”
Section: Materials and Instrumentationmentioning
confidence: 99%
“…29,30 In recent years, research on textile materials has paid great attention to the development of new azomethine dyes for dyeing various fabrics. 31,32 Due to the above and in order to obtain a type of attractive color and safe dyes, we have synthesized azomethine disperse dyes based on pyrazolone moiety which contain iminodiethanol groups by different routes to obtain dyes used for dyeing polyester fabrics.…”
mentioning
confidence: 99%
“…For example, pyrazolin-5-ones are very important class of heterocycles, due to their potential pharmacological and biological applications [1][2][3][4][5][6][7][8][9]. Moreover, such heterocycles are extensively involved in the manufacture of commercial dyes, such as photographic dyes and textile dyes [10,11]. Azomethine dyes derived from pyrazolone are commonly used in color photography; usually these dyes are magenta in hue [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%